1968
DOI: 10.1172/jci105737
|View full text |Cite
|
Sign up to set email alerts
|

Role of anaerobic metabolism in the preservation of functional capacity and structure of anoxic myocardium

Abstract: A B ST R A CT Employing an isolated perfused rat heart preparation, we investigated the contriblution of anaerobic metabolic energy to the lerformance, recoverability, and ultrastructure of the heart perfused at 320C in 5% albumin in Krebs-Ringer Bicarbonate solution. During exposure to anoxia for 30 min, inclusion in the perfusate of the anaerobic substrate, glucose, resulted in marked improvement in electrical and mechanical performance of the heart and in enhanced recovery during the subsequent period of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Although conflicting results have been obtained in assessing the efficacy of glucose in the treatment of acute coronary ischemia (34)(35)(36), evidence has been provided of prolonged survival of ischemic tissue during glucose treatment (37)(38)(39). The rationale suggested for using glucose or combinations of glucose, K, and insulin in treating myocardial infarction has been to supply adequate glucose to the heart, thereby obtaining energy from anaerobic breakdown of glucose (37,38,40), reverse potassium loss from the heart, and maintain membrane stability (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Although conflicting results have been obtained in assessing the efficacy of glucose in the treatment of acute coronary ischemia (34)(35)(36), evidence has been provided of prolonged survival of ischemic tissue during glucose treatment (37)(38)(39). The rationale suggested for using glucose or combinations of glucose, K, and insulin in treating myocardial infarction has been to supply adequate glucose to the heart, thereby obtaining energy from anaerobic breakdown of glucose (37,38,40), reverse potassium loss from the heart, and maintain membrane stability (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Because lipids are not used as major precursors for anaerobic metabolism, glucose is the primary substrate to support anaerobic metabolism. Thus, anaerobic metabolism with concomitant increased use of glucose, as fostered by Txnip deletion, plays a significant role in preserving myocardial function and structure and in promoting recoverability of the hypoxic heart (35).…”
Section: Figurementioning
confidence: 99%
“…A previous report demonstrated that inclusion of glucose in the perfusate of isolated perfused rat heart preparations results in marked improvement in electrical and mechanical performance of the heart subjected to anoxia and in enhanced recovery during the subsequent period of reoxygenation (35). While lactate production was 5-fold greater in the glucosesupported anoxic heart than in the anoxic heart without glucose, morphologic changes of mitochondria during anoxia were averted by inclusion of glucose in the perfusion fluid (35). Thus, anaerobic metabolism, with concomitant increased use of glucose, can preserve myocardial function and structure and promote ischemic heart recovery.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, infusion of GIK after acute myocardial infarction has been reported to have variable effects in man, producing either beneficial,8-18 deleterious or no effects'9 26 on mortality. Similarly, GIK infusions have produced variable effects on pacing-and exercise-induced angina.…”
Section: Glucose-insulin-potassium (Gik)mentioning
confidence: 99%